Mycobacterium tuberculosis Mannose-Capped Lipoarabinomannan Induces IL-10-Producing B Cells and Hinders CD4+Th1 Immunity - Yuan, Chunhui; Qu, Zi-Lu; Tang, Xiao-Lei; Liu, Qi; Luo, Wei; Huang, Chun; Pan, Qin; Zhang, Xiao-Lian (iScience, 2019)
The importance of Th1/interferon (IFN)-γ-mediated responses in mycobacterial infection has been well established. However, little is known about B cell-mediated immunity during Mycobacterium tuberculosis (Mtb) infection. Interleukin (IL)-10-producing B cells (B10 cells), a subset of B regulatory cells (Bregs), are implicated in modulating the immune response. Herein, we found that B10 cells were significantly increased in patients with tuberculosis. Furthermore, mannose-capped lipoarabinomannan (ManLAM), a major surface lipoglycan component from Mtb, induced a significant increase in B10 cells, which enriched in CD5+ B1a B cells. ManLAM induced IL-10 production mainly by activating MyD88/PI3K/AKT/Ap-1 and K63-linked ubiquitination of NF-κB essential modulator/nuclear factor kappa-light-chain-enhancer of activated B cells signaling pathways in B cells via Toll-like receptor 2. IL-10 production by ManLAM-treated B cells further inhibited CD4+ Th1 polarization, leading to increased susceptibility to mycobacterial infection compared with ManLAM-treated IL-10−/− B group. Thus, we report a new immunoregulation mechanism in which Mtb ManLAM-induced B10 cells negatively regulate host anti-TB cellular immunity. [Display omitted] •Mtb mannose-capped lipoarabinomannan (ManLAM) induces IL-10 production in B cells•ManLAM-induced B10 cells enrich in CD5+ B1a B cells•ManLAM binding with TLR2 triggers MyD88 signaling pathways of B cells•ManLAM-induced B10 cells hinder CD4+Th1 immunity during Mtb infection in mice Bacterium; Biological Sciences; Immune Response; Microbiology